Group theoretic cryptography - González Vasco, Maria Isabel; Steinwandt, Rainer (Chapman & Hall/CRC cryptography and network security., 2015)
"Supplies an introduction to cryptography for those interested in group theory -- Offers formal security analyses and highlights potential vulnerabilities for cryptographic constructions involving group theory -- Provides full proofs of important theorems -- Emphasizes algorithmic aspects -- Includes problems and selected solutions"--